A behavioral heterogeneous agent New Keynesian model - Oliver Pfäuti; Fabian Seyrich (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We develop a New Keynesian model with household heterogeneity and bounded rationality in the form of cognitive discounting. The interaction of household heterogeneity and bounded rationality generates amplification of monetary and fiscal policy through indirect general equilibrium effects while simultaneously ruling out the forward guidance puzzle and remaining stable at the effective lower bound. Thus, the model can account for recent empirical findings on the transmission mechanisms and effectiveness of monetary and fiscal policy. When abstracting from either household heterogeneity or bounded rationality the model fails to do so. Our framework nests a broad range of existing models, none of which can be consistent with all these empirical facts simultaneously. According to our model, central banks have to increase interest rates more strongly than in the rational model after an inflationary supply shock to fully stabilize inflation. While fully stabilizing inflation keeps output at potential, higher real interest rates mainly benefit wealthy households and increase the cost of government debt, leading to a substantial increase in government debt and inequality. Our model thus indicates a more pronounced trade off between aggregate efficiency and price stability on one hand, and distributional consequences and fiscal sustainability on the other hand.
Keywords: E21; E52; E62; E71; 330; Heterogeneous Households; Behavioral Macroeconomics; Monetary Policy; Forward Guidance; Fiscal Policy; Lower Bound; Inflation; Macroeconomic Stabilization